Effect of Rotary Instrument Associated with Different Irrigation Techniques on Removing Calcium Hydroxide Dressing - Faria, Gisele [UNESP]; Viola, Kennia Scapin [UNESP]; Kuga, Milton Carlos [UNESP]; Aranda Garcia, Arturo Javier [UNESP]; Daher, Vanessa Bossolani; De Pasquali Leonardo, Mario Francisco; Tanomaru-Filho, Mario [UNESP] (Wiley-Blackwell, 2014)
Calcium hydroxide [Ca(OH)(2)] residues in root canals may compromise sealing of filling and endodontic treatment success. The aim of this study was to compare the efficacy of using rotary instrument associated with EndoActivator, EndoVac, passive ultrasonic irrigation (PUI), and conventional needle irrigation (CNI), in Ca(OH)(2) removal from root canal, by means of scanning electron microscopy (SEM) images. Sixty-six human canines were prepared with the Protaper system up to F5 and filled with Ca(OH)(2). After 7 days, Ca(OH)(2) was removed with rotary instrument F5 associated with the irrigation techniques used in each group (n = 15): GI (CNI), GII (EndoVac), GIII (EndoActivator) and GIV (PUI). In all groups 15 mL of 2.5% NaOCl and 3 mL of 17% EDTA were used for Ca(OH)(2) removal. The Ca(OH)(2) residues was evaluated by SEM in the middle and apical third using a system of scores. The results were analyzed by the Kruskal-Wallis and Dunn tests (alpha = 0.05). None of the techniques completely removed the Ca(OH)(2) from root canals. There was no difference between EndoActivator, EndoVac and PUI (P > 0.05), but the three techniques removed more Ca(OH)(2) than the CNI (P < 0,05), in the middle and apical thirds of the root canal. It was concluded that the rotary instrument combined with EndoActivator, EndoVac, and PUI was shown to be more efficient than the rotary instrument combined with the CNI in removing Ca(OH)(2) from the root canal. (C) 2014 Wiley Periodicals, Inc.
Keywords: scanning electron microscopy; calcium hydroxide; irrigation; rotary instrument